2010
DOI: 10.1117/1.3316499
|View full text |Cite
|
Sign up to set email alerts
|

High-sensitivity, wide-dynamic-range avalanche photodiode pixel design for large-scale imaging arrays

Abstract: Abstract. We present a detailed design study for a novel solidstate focal plane array of silicon avalanche photodiodes (APDs), with each detector in the array IntroductionThere is a growing need in science and industry for largescale detector arrays capable of imaging with high sensitivity and high speed near room temperature, over a wide range of natural illumination conditions from direct sunlight to a cloudy moonless night. Existing solid-state camera technology does not enable imaging in the visible spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…The quantum efficiency of the 27 μm emitter-detector pixel with etched laser diode cavity has a reduced quantum efficiency for the visible and near infrared wavelengths compared to a silicon mesa detector pixel without an etched cavity for the laser diode. 5,8 At the GaN-VCSEL diode wavelength of emission however, the sapphire microlens helps to focus light into the APD silicon and away from the crystallographically etched laser diode cavity, thereby preserving high detector quantum efficiency at the laser wavelength. The Si-ðAlN∕a-SiN 0.62 Þ-sapphire-(MgF 2 ) substrate enables nearly two times as much light to be transmitted into the APD detector at the laser wavelength λ 0 ¼ 370 nm compared to Si-(AlN)-sapphire-(MgF 2 ), thereby improving the unity SNR threshold of the 27 μm emitter-detector pixel to a maximum possible range of 27,500 m. The improvement in the detection range of the optical radar pixel photonic device can be regarded as significant.…”
Section: Sensitivity Of the Active Emitter-detector Pixelmentioning
confidence: 99%
See 4 more Smart Citations
“…The quantum efficiency of the 27 μm emitter-detector pixel with etched laser diode cavity has a reduced quantum efficiency for the visible and near infrared wavelengths compared to a silicon mesa detector pixel without an etched cavity for the laser diode. 5,8 At the GaN-VCSEL diode wavelength of emission however, the sapphire microlens helps to focus light into the APD silicon and away from the crystallographically etched laser diode cavity, thereby preserving high detector quantum efficiency at the laser wavelength. The Si-ðAlN∕a-SiN 0.62 Þ-sapphire-(MgF 2 ) substrate enables nearly two times as much light to be transmitted into the APD detector at the laser wavelength λ 0 ¼ 370 nm compared to Si-(AlN)-sapphire-(MgF 2 ), thereby improving the unity SNR threshold of the 27 μm emitter-detector pixel to a maximum possible range of 27,500 m. The improvement in the detection range of the optical radar pixel photonic device can be regarded as significant.…”
Section: Sensitivity Of the Active Emitter-detector Pixelmentioning
confidence: 99%
“…5,8 It has been shown that the silicon mesa APD will operate with high quantum efficiency and the array will achieve 100% sensitive-area-fill-factor due to the antireflective layer between the sapphire and silicon and due to the spherical sapphire microlens. In the conventional silicon mesa APD, the microlens focuses optical rays under full height of the silicon mesa and away from the mesa sidewalls that have a reduced height as well as away from the optical dead space between pixels where the silicon has been etched, to enable low resistance anode contacts and direct pixel-topixel optical crosstalk isolation.…”
Section: Silicon Avalanche Photodiode Designmentioning
confidence: 99%
See 3 more Smart Citations